Publicidade e feminismos : tramas da campanha "Reposter, redondo é sair do seu passado" da Skol - Gracila Ferreira Vilaça (2020)
In 2017, the beer brand Skol – which at that point was the most valuable in Brazil – adhered to what is now understood as female empowerment advertising campaigns. The company launched the endeavour called “Reposter, redondo é sair do seu passado” on its Facebook page on that year’s International Women’s Day. In doing so, Skol associated itself to the semantics of feminist movements in order to move away from the sexist and racist past of the brand – which now and again was revisited to shape Skol’s most recent proposals of social interactions. When such a social actor – that historically favoured men’s sociability at the price of objectifying women – relates advertisement and feminisms in order to give new meanings to its past, tensions between such disparate textual networks are stressed. Reposter is striking as an important exponent of those contemporary tensions and tendencies. For that reason the campaign is investigated with the objective of discussing the association, conformation, information, and actualization of feminists movements and women’s corporeality. In that sense, its constitutive parts are explored as perceivable units of a communicational fabric that enables its existence and signification. Consequently, they weave as well as they are multimodal regarding their verbal-audio-visual configurations; provoking the senses, and enabling contextual, reflexive and discursive readings. From these conceptualizations, the theoretical-methodological gesture emerges aiming to open the textual networks of both advertisement and feminisms in a way that they can be relativized, demonstrating that there is a certain history between them that focus on consumption as an important point of contact. That notion of textual fabrics also supports the critical articulation between more objective parts of the corpus – the texts –, which is composed by a main making-of video, eight secondary videos and 16 posters. And, seeking for meanings that go beyond the beer’s intentionality over the female body, an atlas was developed in order to enable the visualization of the social memory that the images of the posters enable, on different types of media.